2016
DOI: 10.1007/s10633-016-9524-3
|View full text |Cite
|
Sign up to set email alerts
|

Is multifocal electroretinography an early predictor of glaucoma?

Abstract: Alterations of amplitudes and implicit times of N2 response in the central area may be able to detect glaucoma earlier than VFA. In addition, with progression to advanced glaucoma these changes can be significant in all retinal areas. Although implicit times of all mfERG components are significantly delayed in glaucoma, both delayed implicit time and decreased amplitude of N2 wave in the central area are effective predictors in early glaucoma diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Gölemez et al measures the sensitivity of mfERG in diagnosis, especially in suspected cases. The authors observed that especially the N2 amplitudes were decreased in the central ring (5 degrees) in the early stage and in all rings in advanced-stage patients compared with the control group [15]. In our study, when the mfERG parameters of the patients were compared between the early and middle-advanced glaucoma groups, there was no significant difference in the amplitudes of the N1-P1-N2 waves and implicit time.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Gölemez et al measures the sensitivity of mfERG in diagnosis, especially in suspected cases. The authors observed that especially the N2 amplitudes were decreased in the central ring (5 degrees) in the early stage and in all rings in advanced-stage patients compared with the control group [15]. In our study, when the mfERG parameters of the patients were compared between the early and middle-advanced glaucoma groups, there was no significant difference in the amplitudes of the N1-P1-N2 waves and implicit time.…”
Section: Resultscontrasting
confidence: 58%
“…As a potentially effective procedure, mfERG produces the simultaneous records of focal retinal response in many different retinal regions and shows the topographic representations of retinal response components [12,13]. The early detection of retinal dysfunction is recommended for the diagnosis of early stage glaucoma [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The mfERG is a validated methodology for clinical evaluation of several conditions, including retinitis pigmentosa, hydroxychloroquine toxicity, glaucoma, ocular vascular occlusive disorders [22][23][24][25][26][27] . Reveling subclinical abnormalities of retinal function, mfERG can identify patients at risk of retinal damage progression allowing for early therapeutic interventions [28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the mfERG N2 component is analogous to the PhNR of the ff-ERG [Viswanathan S, et al IOVS 2009;50: ARVO E-Abstract 4758], which in turn may share retinal generators with the PERG N95 [38,56]. Thus it is not surprising that the mfERG N2 appears to reflect glaucomatous damage [23,57,58]. Significant reduction of LFC amplitudes in mfERG responses to a more complicated stimulus have also been reported in NHP EG [41], which might reflect a similar underlying functional abnormality.…”
Section: Discussionmentioning
confidence: 99%